2016
DOI: 10.1371/journal.pone.0147336
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Caco-2 Cancer Cell Line following Treatment with Extracts from Iodine-Biofortified Lettuce (Lactuca sativa L.)

Abstract: Although iodization of salt is the most common method used to obtain iodine-enriched food, iodine deficiency disorders are still a global health problem and profoundly affect the quality of human life. Iodine is required for the synthesis of thyroid hormones, which are crucial regulators of human metabolism, cell growth, proliferation, apoptosis and have been reported to be involved in carcinogenesis. In this study, for the first time, we evaluated the effect of iodine-biofortified lettuce on transcriptomic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“… Kopeć et al (2015) revealed higher I assimilability and improvement of this element’s metabolism in rats fed with I-enriched lettuce in relation to those fed with control lettuce and a diet containing mineral KI. In the research by Koronowicz et al (2016) , the inhibition of Caco-2 cancer cell proliferation was demonstrated after treatment with I-biofortified lettuce extract, but not KI as well as I-biofortified lettuce-mediated induction of mitochondrial apoptosis and/or cell differentiation. This study showed 1326 differently expressed Caco-2 transcripts after treatment of biofortified and non-fortified lettuce extract.…”
Section: Discussionmentioning
confidence: 97%
“… Kopeć et al (2015) revealed higher I assimilability and improvement of this element’s metabolism in rats fed with I-enriched lettuce in relation to those fed with control lettuce and a diet containing mineral KI. In the research by Koronowicz et al (2016) , the inhibition of Caco-2 cancer cell proliferation was demonstrated after treatment with I-biofortified lettuce extract, but not KI as well as I-biofortified lettuce-mediated induction of mitochondrial apoptosis and/or cell differentiation. This study showed 1326 differently expressed Caco-2 transcripts after treatment of biofortified and non-fortified lettuce extract.…”
Section: Discussionmentioning
confidence: 97%
“…I-enriched lettuce strongly reduces the in vitro development of cancerous cells in colon cancer (Koronowicz et al, 2016). It seems appropriate to study the use of lettuce enriched with 5-ISA and 3,5-diISA in nutrigenomics.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…According to the literature, flavonoids present in lettuce extracts could exhibit in vitro toxic effects against human hepatoma (HepG2) cells [83], however the main compound responsible for these effects was luteolin-7-O-glucoside which was not detected in our study. Moreover, extracts from iodine-biofortified lettuce were effective against Caco-2 cancer cell line [84], while Durazzo et al [85] suggested significant effects of cultivation practices on cytotoxicity of lettuce extracts against the same cell line. Similarly to our study, Karkanis et al [82] reported a significant impact of growth substrate on the cytotoxic effects of Sanguisorba minor leaf and root extracts, which indicates that differences in the physicochemical properties of the growing medium may affect the bioactivities of the final produce.…”
Section: Controlmentioning
confidence: 99%